Platelet-Depletion of Whole Blood Reveals That Platelets Potentiate the Release of IL-8 From Leukocytes Into Plasma in a Thrombin-Dependent Manner - Quach, Huy Quang; Johnson, Christina; Ekholt, Karin; Islam, Rakibul; Mollnes, Tom Eirik; Nilsson, Per H. (Frontiers in Immunology, 2022)
Objective: In a recent study, we found an elevated level of interleukin 8 (IL-8) in response to bacterial incubation in thrombin-sufficient human whole blood anticoagulated by the fibrin polymerization blocking peptide GPRP. Whether thrombin directly activated leukocytes or mediated the release via thrombin-dependent activation of platelets remains unresolved. Herein, we addressed the role of thrombin and platelets in IL-8 release. Methods: We separated platelets from whole blood using a combination of 0.7% (w/v) citrate and GPRP for attenuating the hemostatic response during the separation of platelets. Cytokine responses were compared in whole blood and platelet-depleted blood upon Escherichia coli incubation. Cytokine responses were also profiled with and without reconstitution of either platelets or the supernatant from activated platelets. Results: Platelets were not activated during the separation process but responded to stimuli upon re-calcification. Plasma levels of IL-1, IL-1Ra, IL-6, IL-8, IP-10, MIP-1, and MIP-1 were significantly reduced in platelet-depleted blood compared to whole blood, but recovered in the presence of platelets, or with the supernatant of activated platelets. The leukocyte fraction and platelets were each found to contribute to the elevation of IL-8 at around 5 ng/ml; however, if combined, the release of IL-8 increased to 30 ng/ml. This process was dependent on thrombin since the levels of IL-8 remained at 5 ng/ml in whole blood if thrombin was blocked. Conclusion: Our findings suggest that the release of IL-8 is mediated by the leukocytes, but potentiated via thrombin-dependent activation of platelets.